Bright white up-conversion emission from sol-gel derived Yb3+/Er3+/Tm3+: Y2SiO5 nanocrystalline powders - EKMEKÇİ, METE KAAN; ERDEM, MURAT; GENÇ, SEVAL (ELSEVIER SCI LTD, 2015)
Bright white up conversion emission has been observed in sol gel derived Yb3+/Er3+/Tm3+: Y2SiO5 nanocrystalline powders when excited with the 950 nm emission of a laser diode. Measurements of the sample emission intensity dependence on the pumping power were performed to explain the up conversion mechanism. The CIE chromaticity coordinates (x, y) for white emission in X-2-Y2SiO5 nanocrystalline form were found to be (0.334, 0.332) under 950 nm laser diode excitation. (C) 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Upconversion; Sol-gel; Nanophosphors; White light; BLUE PHOSPHOR Y2SIO5-CE; LUMINESCENT PROPERTIES; COMBUSTION SYNTHESIS; LIGHT EMISSION; POLYCRYSTALS; LA; SC